Hyaluronan, a Crucial Regulator of Inflammation - Petrey, Aaron C.; de la Motte, Carol A. (Frontiers in Immunology, 2014)
Hyaluronan (HA), a major component of the extracellular matrix (ECM), plays a key role in regulating inflammation. Inflammation is associated with accumulation and turnover of hyaluronan polymers by multiple cell types. Increasingly through the years, HA has become recognized as an active participant in inflammatory, angiogenic, fibrotic, and cancer promoting processes. HA and its binding proteins regulate the expression of inflammatory genes, the recruitment of inflammatory cells, the release of inflammatory cytokines, and can attenuate the course of inflammation, providing protection against tissue damage. A growing body of evidence suggests the cell responses are HA molecular weight dependent. Hyaluronan fragments generated by multiple mechanisms throughout the course of inflammatory pathologies, elicit cellular responses distinct from intact hyaluronan. This review focuses on the role of hyaluronan in the promotion and resolution of inflammation.